Welding Current Variation Determines Tensile Strength of Low Carbon Steel: Variasi Arus Las Menentukan Kekuatan Tarik Baja Karbon Rendah - Slamet Fauji Riyanto; Jamaaludin (Universitas Muhammadiyah Sidoarjo, 2026)
This study examines the relationship between welding current variation and the tensile strength of low carbon steel joints. General Background: Welding is a critical process in manufacturing industries, where joint strength determines structural reliability. Specific Background: Shielded Metal Arc Welding (SMAW) is widely used due to its flexibility, but welding parameters such as current significantly affect joint quality. Knowledge Gap: Previous studies have discussed welding parameters, yet limited focus is given to specific current variations and their direct relation to tensile strength in certain steel materials. Aims: This research aims to analyze the effect of different welding current levels on the tensile strength of low carbon steel. Results: The findings indicate that variations in welding current produce different tensile strengths, with a specific current level yielding the highest strength, while excessively high or low currents reduce joint performance. Novelty: The study provides focused experimental evaluation of current variation on tensile strength using controlled parameters in SMAW welding. Implications: The results offer practical guidance for selecting appropriate welding current to achieve optimal mechanical properties in industrial applications. Keywords: Welding Current, Tensile Strength, Low Carbon Steel, SMAW Welding, Mechanical Properties Key Findings Highlights Different current levels produce distinct mechanical responses in welded joints Peak strength occurs at a specific parameter setting during testing Improper current selection leads to reduced joint performance